2021
DOI: 10.3390/en14175274
|View full text |Cite
|
Sign up to set email alerts
|

Study on Comprehensive Performance of Three-Dimensional Tube Applied to Gas–Solid Two-Phase Flow Environment

Abstract: The three-dimensional tubular heat exchanger has excellent performance in single-phase flow, but its performance in gas solid two-phase flow is still lacking research. In this paper, analysis and comparison of heat exchanger prototypes made up of four different three-dimensional tubes by different comprehensive performance evaluation methods are carried out through experimental research and theoretical analysis. The research results show that the ratio of the long axis to the short axis of the three-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Liu et al [24] found that the shell-side heat-transfer coefficient per unit pressure drop of the twisted-elliptic-tube oil cooler is larger than traditional heat exchangers with segmental baffles. Mo et al [25] studied the heat-transfer and fluid flow performance of the twisted elliptic tube in the gas-solid two-phase flow environment. Al-Hadhrami et al [26] evaluated the performance of a twisted-elliptic-tube heat exchanger of an existing naphtha hydrotreating plant.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [24] found that the shell-side heat-transfer coefficient per unit pressure drop of the twisted-elliptic-tube oil cooler is larger than traditional heat exchangers with segmental baffles. Mo et al [25] studied the heat-transfer and fluid flow performance of the twisted elliptic tube in the gas-solid two-phase flow environment. Al-Hadhrami et al [26] evaluated the performance of a twisted-elliptic-tube heat exchanger of an existing naphtha hydrotreating plant.…”
Section: Introductionmentioning
confidence: 99%